Translating the Hebrew Bible in medieval Iberia: Oxford, Bodleian Library, MS Hunt. 268 - Alfonso, Esperanza (The Iberian religious world, 2021)
"Translating the Hebrew Bible in Medieval Iberia provides the princeps diplomatic edition and a comprehensive study of Oxford, Bodleian Library, MS Hunt. 268. The manuscript, produced in the Iberian Peninsula in the late thirteenth century, features a biblical glossary-commentary in Hebrew that includes 2,018 glosses in the vernacular and 156 in Arabic, and to date is the only manuscript of these characteristics known to have been produced in this region. Esperanza Alfonso has edited the text and presents here a study of it, examining its pedagogical function, its sources, its exegetical content, and its extraordinary value for the study of biblical translation in the Iberian Peninsula and in the Sephardic Diaspora. Javier del Barco provides a detailed linguistic study and a glossary of the corpus of vernacular glosses"--